Pengaruh Keselamatan dan Kesehatan Kerja Terhadap Produktivitas Kerja Karyawan - M. Fajar Nugroho; Rakhmat Haryono (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2020)
The purpose of this research is to investigate and analyze how occupational safety, occupational health and work productivity, and the influence of occupational health and safety to work productivity in one the private hospitals in Bandung, either simultaneously or partially. Type of this research is quantitative research and the method used in this research is survey descriptive and verification method. Independent variables in this research are Occupational Safety (X1) and Occupational Health (X2), and the dependent variable is labour productivity (Y). Respondent who used were employees in one of the private hospitals in Bandung with the number of samples were 280 people selected by simple random sampling techniques with the help of Isaac and Michael tabel. The data used are primary and secondary data. The main instrument of thi research is the questionnaire. To test the validity instrument is using Product Moment Pearson and the realibility using a - Cronbach. The statistical hypothesis is using path analysis. The research result shows that the occupational safety and health partially and simultaneously have an effect on work productivity. Partially, occupational safety have a more dominant effect on work productivity compared with occupational health.